(untitled) (Clinics, 2015)
OBJECTIVES: To investigate the prevalence of excess body weight in the pediatric ward of University Hospital and to test both the association between initial nutritional diagnosis and the length of stay and the in-hospital variation in nutritional status. METHODS: Retrospective cohort study based on information entered in clinical records from University Hospital. The data were collected from a convenience sample of 91 cases among children aged one to 10 years admitted to the hospital in 2009. The data that characterize the sample are presented in a descriptive manner. Additionally, we performed a multivariate linear regression analysis adjusted for age and gender. RESULTS: Nutritional classification at baseline showed that 87.8% of the children had a normal weight and that 8.9% had excess weight. The linear regression models showed that the average weight loss z-score of the children with excess weight compared with the group with normal weight was −0.48 (p = 0.018) and that their length of stay was 2.37 days longer on average compared with that of the normal-weight group (p = 0.047). CONCLUSIONS: The length of stay and loss of weight at the hospital may be greater among children with excess weight than among children with normal weight.